Is Malaysia ready for Industry 4.0? Issues and Challenges in Manufacturing Industry - Ling, Yong Ma; Abdul Hamid, Nor Aziati; Chuan, Lee Te (International Journal of Integrated Engineering, 2020)
Despite as a strong manufacturing economist in ASEAN, manufacturers in Malaysia are the beginners who are lack of proper understanding of the concepts and practices of Industry 4.0. The purpose of this paper is to identify the issues and challenges of Industry 4.0 from industry-based companies' aspect by conducting a literature review. This paper also highlighted the comparison between the potential challenges stated in the Malaysia National Policy on Industry 4.0 with the challenges proposed by previous studies of other countries. This paper is a literature review on previous studies regards to challenges or issues on implementation of Industry 4.0 from 2015 to 2019. Total 11 challenges in the processes of implementation Industry 4.0 into manufacturing companies are reviewed. Compared to previous studies, Malaysia National Policy on Industry 4.0 overlooked 3 challenges on Industry 4.0. This is the first review paper to compare the existing challenges in Industry 4.0 with the potential challenges stated in the Malaysia National Policy on Industry 4.0.